Modulation of trail laying in the ant Lasius neglectus (Hymenoptera: Formicidae) and its role in the collective selection of a food source. (14th November 2018) - Frizzi, Filippo; Talone, Francesco; Santini, Giacomo
Abstract: In this study, we explored the feeding behaviour of the invasive garden ant Lasius neglectus . In particular, we investigated its ability to select the more profitable resource in a binary choice and its pheromonal trail marking. When facing a choice between two different energy sources, workers were rapidly recruited to the most profitable one, although both the speed of the recruitment and the number of ants varied considerably with the difference between the solutions. When facing two identical sources, workers were massively recruited onto one of the two in 80% of tests, whereas in the remaining 20% the workforce was split equally between the two. In the second experiment, we supplied a single food source and then assessed if the number of marks per ant was affected by solution concentration and direction of movement (nestward or foodward), and if it varied over time. Marking activity increased with solution concentration, was more intense in nestward‐moving ants, and decreased over time. All these effects, although significant, were not pronounced. However, the marking activity of the very first ants visiting the resource was more intense, and this seems to be sufficient to explain the collective selection of the most valuable resource. Finally, marks were not evenly distributed along the trail, but concentrated at some points. The behaviour of L. neglectus is partly comparable to that of Lasius niger, but appears to be more similar to that of other invasive ant species, suggesting a possible primary role of the marking behaviour in influencing the invasiveness of this species.